Atrophic dermatofibroma - Amanda Nascimento C. de Macedo Mota; Violeta Duarte Tortelly; Daniel Lago Obadia; Roberto Souto da Silva (Sociedade Brasileira de Dermatologia, 2013)
Dermatofibroma is a benign fibrohistiocytic tumor, common and easily diagnosed when classical clinicopathologic features are present. The atrophic variant of dermatofibroma is of uncertain origin. This lesion is characterized clinically by a flat or atrophic and depressible surface. Histopathological features show reduction of the thickness of the dermis and elastic fibers. We report a typical case of this uncommon and probably underdiagnosed variant.